The Implementation of Financial Technology in Improving Digital Financial Understanding Among Accounting Students in South-East Asia with Technology Acceptance Model Approach - Renaldo, Nicholas; Junaedi, Achmad Tavip; Tanjung, Amries Rusli; Augustine, Yvonne; Suhardjo, Suhardjo; Musa, Sulaiman; Cecilia, Cecilia (First Ciera Publisher, 2025)
This research analyzes the impact of FinTech Implementation on the digital financial understanding of accounting students in Southeast Asia. Novelty of this research is to develop a new measurement by adding 3 new dimensions to the Financial Technology Implementation variable and 2 new dimensions to Digital Finance Understanding variable. This research used Technology Acceptance Model (TAM) approach. This study employs a quantitative approach with qualitative support, using PLS-SEM as the primary analytical method. The quantitative approach is used to analyze relationships between variables, while the qualitative method provides deeper insights into students' experiences with FinTech adoption. Population in this study are accounting students in Southeast Asia, particularly in Indonesia, Malaysia, Singapore, Thailand, Brunei Darussalam, and Philippines. Purposive sampling is used to select students from universities with accounting programs and targets 320 respondents. The implementation of Financial Technology (FinTech) significantly enhances Digital Financial Understanding (DFU) by improving financial literacy, accessibility, and user engagement with digital financial services. FinTech platforms, such as digital banking apps, investment platforms, and robo-advisors, provide real-time financial insights, interactive financial tools, and educational resources. The dimensions that are novelty in this study, namely Adoption Intention (X5), Actual Usage (X6), Regulatory Awareness (X7), Digital Financial Behavior (Y4), Regulatory and Consumer Protection Awareness (Y5) have been successfully measured well and become variables that support expansion tests. Future research should examine how FinTech engagement influences financial understanding over an extended period.